A green and facile method toward synthesis of waste paper-derived 3D functional porous graphene via in situ activation of cobalt(ii)1. Issue 31 (21st August 2015) - Xu, Dan; Xie, Yan; Song, Yu-Jiang; Deng, Wei-Qiao
<x xml:space="preserve">Abstract</x> Using waste paper as a carbon source, a strategy for the efficient production of Co3O4/Co@porous graphene as a catalyst for the oxygen reduction reaction was developed, which provides a direction for facile preparation of functional porous graphene from wastes.